2012
DOI: 10.1016/j.mod.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signaling in the visceral muscle is required for left–right asymmetric development of the Drosophila midgut

Abstract: Many animals develop left-right (LR) asymmetry in their internal organs. The mechanisms of LR asymmetric development are evolutionarily divergent, and are poorly understood in invertebrates. Therefore, we studied the genetic pathway of LR asymmetric development in Drosophila. Drosophila has several organs that show directional and stereotypic LR asymmetry, including the embryonic gut, which is the first organ to develop LR asymmetry during Drosophila development. In this study, we found that genes encoding com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 104 publications
10
56
0
Order By: Relevance
“…To elucidate the genetic mechanisms of LR asymmetric development in Drosophila , we carried out a genetic screen to find mutants showing LR asymmetric defects of the embryonic gut (Hozumi et al, ; Kuroda et al, ; Maeda et al, ; Nakamura et al, ; Okumura et al, ; Taniguchi et al, ). From this screen, we identified a novel allele of emc , emc tink .…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the genetic mechanisms of LR asymmetric development in Drosophila , we carried out a genetic screen to find mutants showing LR asymmetric defects of the embryonic gut (Hozumi et al, ; Kuroda et al, ; Maeda et al, ; Nakamura et al, ; Okumura et al, ; Taniguchi et al, ). From this screen, we identified a novel allele of emc , emc tink .…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila Wnt4 has been shown to function through both canonical (Kuroda et al, 2012) and non-canonical Wnt signaling pathways (Cohen et al, 2002; Harris and Beckendorf, 2007; Lim et al, 2005). We genetically manipulated different Wnt signaling components to determine the pathways active in heart development.…”
Section: Resultsmentioning
confidence: 99%
“…Drosophila Wnt4 is most closely related to vertebrate Wnts 9, 14 and 15 (Prud'homme et al, 2002) and has been shown to be involved in the development of dorsal epidermis, retina, heart and ovaries as well as in the left-right asymmetric morphogenesis of the midgut (Cohen et al, 2002; Hamada-Kawaguchi et al, 2014; Inaki et al, 2007; Kuroda et al, 2012; Wu et al, 2013). Wnt4 was shown to bind to both the Fz1 and Fz2 receptors (Wu and Nusse, 2002) and to signal through both the canonical and non-canonical Wnt pathways, depending on cellular contexts (Cohen et al, 2002; Hamada-Kawaguchi et al, 2014; Wu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%